AKSENTUASI NILAI NORMATIF RASULULLAH: (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
Fethullah Gulen is a well-known religious leader and Islamic preacher in Turkey. Gülen is well renowned for his "love of fellow human beings," in addition to his emphasis on Islamic spirituality (sufism). This article examines the emphasisualization of the Prophet's normative norms as the foundation for the actualization of Fethullah Gulen's da'wah. The research approach employed is a literature review, with research sources originating from documents, magazines, thesis or thesis research outcomes, and conference results. According to the study's findings, the Gülen movement is well-known for delivering a holistic education that integrates intellectual and spiritual components. The implementation of Gülen's da'wah focuses on merging modern science with Islamic precepts.Fethullah Gulen has, however, come under heavy criticism for being the Gulen Movement's creator ever since it began. Since Gulen is viewed as a danger to Turkey's secular system, secularists in Turkey have denounced him. Keywords: accentuation, Rasullullah, actualization, da'wah, Fethullah Gulen